ANALYSIS OF THE TRANSFORMATION OF LEARNING IN THE CONTEXT OF DIGITALIZATION OF EDUCATION - Ibragimov Shavkat Mamirovich (Academia Science Repository, 2023)
The article is devoted to the problem of digitalization of the education system at the present stage of development of society. In particular, it is noted that digitalization is aimed at training specialists who are guaranteed to be in demand in the labor market, who are easily and fluent in mobile and Internet technologies. In the age of informatization and digitalization, the teacher himself must change. He should develop new methods and forms of education. Attention is drawn to the advantages of digitalization of education and some of its disadvantages.